Sharia and National Law in Muslim Countries. Tensions and Opportunies for Dutch and EU Foreign Policy - Otto, Jan Michiel (Law, Governance, and Development, 2008)
The relationship between 'Islam and the West' has become a central issue in international relations. Recently, an overwhelmingly negative view of sharia has developed in the West, in response to reported events, notably in Iran and Saudi Arabia, to terrorist attacks by Islamists, and also encouraged by certain Western opinion leaders. A range of misconceptions about what sharia actually means and how it relates to national law in Muslim countries, both in theory and practice, has contributed to foreign policies that are confrontational rather than pragmatic. This Research and Policy Note identifies key features, problems and approaches of sharia-based law and links them to foreign policy. This is a vital contribution towards the development of a well-informed, coherent, explicit long-term foreign policy towards the Muslim world.